Strategic Organisational Communication and Leadership in a Sufi Institution: A Case Study of the Naqshabandiyyah Centre in Negeri Sembilan, Malaysia - Abdul Hamid, Mohammad Fahmi; Sharipp, Muhammad Taufik Md; Ab Ahmid, Muhammad Iskandar Shah; Ichwan, Moh. Nor (Jurnal Theologia, 2025)
This study addresses the crucial issue of communication inefficiencies within religious organisations, which often lead to leadership fragmentation, operational confusion, and public misperception. Focusing on the Naqshabandiyyah Sufi Practice Centre (NSPC) in Negeri Sembilan, Malaysia, the research explores how strategic organisational communication enhances management decision-making in a spiritually structured institution. The objective is to analyse the roles of vertical and horizontal communication in ensuring administrative fluidity, leadership continuity, and public trust in the tarekat’s leadership. Employing a qualitative, descriptive-exploratory approach, the study utilizes document and content analysis to examine internal communications and management practices. The findings reveal that vertical communication supports the clear delegation of authority, vision alignment, and structured leadership formation, while horizontal communication facilitates collaboration, social outreach, and inter-agency coordination. The study also highlights how communication practices rooted in spiritual wisdom contribute to institutional legitimacy and organisational effectiveness. Ultimately, this article contributes to the field of Islamic management and communication by proposing a two-way, value-based communication model suited to the complexities of contemporary spiritual institutions operating within modern governance frameworks.